Pilot Study on Carbon Footprint of Small-Scale Beef Cattle Production at South-West Region of Bangladesh - Das, N G; Sultana, N; Islam, M T; Kabir, M A; Hossain, S M J (Bangladesh Journal of Livestock Research, 2022)
The study was conducted to investigate feed basket composition, greenhouse gas (GHG) emission factors and carbon footprint of beef cattle production at Khulna division, Bangladesh. Data were collected on herd structure, farm feedstuff, manure management and farm operation of 231 beef cattle farms by interviewing farmers and filling up open questionnaires. The feed basket of 75 beef cattle of different genotypes in 24 farms was studied by keeping a record of individual feedstuff intake for three months. Results indicated that the feed basket of a 321 (±131) kg beef cattle, irrespective of genotype, was consisted of rice straw, Napier grass, maize fodder, jumbo grass and concentrate mixture at 3.61 (±1.60), 3.25 (±4.66), 0.21 (±1.34), 0.07 (±0.58), 1.73 (±3.08) and 3.69 (±1.40) kg/d, respectively. The digestibility of diet, volatile solids in manure and nitrogen excretion rate were estimated as 65 (±3.89) %, 8.3 (±2.01) and 0.29 (±0.07) kg/d/1000 kg LW, respectively. The emission factors of enteric CH4, manure CH4 were 46 (±18), and 9.06 (±10.86) kg CH4/yr/animal. The direct and indirect N2O emission factors due to volatilization and leaching were 2.96 (±0.01), 0.06 (±0.07) and 0.017 (±0.019) kg N2O/yr/animal, respectively. Based on the results of emission factors, including the carbon footprint of farm feedstuff (0.33 (±0.33) kg CO2e/yr/t fresh) and farm operation emission factor (131 (±109) kg CO2e/yr/cattle), the carbon footprint of beef cattle production was estimated as 7.68 (±0.98) kg CO2e/kg LW of beef cattle. Estimation of GHG emission factors for all sources in each livestock enterprise, and then accounting for carbon footprint may help realize the environmental cost of production and undertake appropriate mitigation measures. Bang. J. Livs. Res. Vol. 29 (1&2), 2022: P. 34-52